Financial Modeling : step -by-step guide to building your first financial model and value companies from scratch.. - Fairy Panchal (Zebra Learn, 2022)
This book is the ultimate tool for young finance professionals & aspirants looking to break into the financial industry. Financial modeling is considered one of the key skills for any finance role especially because it helps take financial decisions & build strategies. Learn to build financial models from scratch with our step-by-step guide. This book is not a theory book, it's a hands-on boot camp where you work on a real company and build a real financial model as you read. Detailed instructions, downloadable templates, and embedded video course make this book beginner-friendly and 100% actionable. You start with building a solid foundation, extracting raw data & understanding the balance sheet, income statement, and cash flow statements. After that, you move to such as discounted cash flow (DCF) modeling and valuation techniques - key elements of a model. This book is a must-read for young finance professionals and aspirants seeking a career in investment banking, financial analysis, and portfolio management. Boost your resume and gain a competitive edge in the industry with the skills and knowledge gained from this book.
Keywords: Management